Aprender a ensinar Matemática: a participação de estudantes de Pedagogia em uma Comunidade de Prática - Lacerda, Sara Miranda de (2017)
The theme of this research is the teaching training and the learning to teach Mathematics of students of Pedagogy when participating in a Community of Practice and accompanying the work of teachers of the initial years of the Elementary School. The focus of the observation were three Pedagogy students participating in the PUC-SP (CoP OBEDUC) core of the Observatory of Education project entitled “Collaborative Network of Practices in Teacher Training to Teach Mathematics: multiple looks, dialogues and contexts”. This thesis aims to identify the contribution of the participation in CoP OBEDUC for the formative process of these students of Pedagogy to teach Mathematics in the initial years of Elementary School. This study is inserted in the context of social learning theory, which considers social participation as an element that promotes learning. It was used the concept of Community of Practice (Etienne Wenger), which integrates the necessary elements to characterize social participation as a process of learning and knowing. The concept of Community of Practice considers these elements – meaning, practice, community and identity – to be deeply intertwined and mutually defining. For this purpose, actions were taken to observe the contribution of practice in the teaching education of the research, considering their experience in CoP OBEDUC. It was proposed an intervention in the classroom, of elaborating a Mathematics task to be developed in pairs formed by a student of Pedagogy and a teacher of the initial years of Elementary School. The process took place in four stages, inspired by the processes of self-confrontation and cross-self-confrontation (Yves Clot), all of them recorded in audio and video, which included the planning of the action, the development of the task in classroom, together with the teacher of the class, a meeting of confrontation for each pair and a general meeting with the participation of members of CoP OBEDUC, the latter two with the analysis of the scenes from the first two. All this process has contributed to teaching training and has promoted learning of teaching to teach Mathematics. The students have felt themselves inserted, identified with the profession, an evidence of the constitution of teaching identity. It was considered that these learning has occurred due to the set of experiences lived during the period in which they participated in CoP OBEDUC and by the influence of the multiple experiences to which they have been exposed during the considered period. The results indicate that the participation in CoP OBEDUC has allowed the reflection and the interaction with peers, promoting teaching learning of both students and experienced teachers, the negotiation of meanings generated in the dual movement of participation and reification, by the constitution of teacher identity and by practice